Consideration of soil in urban planning documents—a French case study - Blanchart, Anne; Consalès, Jean Noël; Séré, Geoffroy; Schwartz, Christophe (Journal of soils and sediments, 2019)
Purpose Given their increasing importance, soils should be considered as valuable resources by those involved in urban planning. Indeed, soils are expected to be multifunctional in order both to ensure sustainable development of human societies and to resist major environmental issues. Through the study of planning documents, this article describes the way in which political intentions impact the preservation of soil as an urban resource. Materials and methods A lexical analysis was conducted of more than 100 French planning documents. Each of them relates to a specific topic (e.g., soil cover, transport, biodiversity) and to a particular application scale. Tropes© software was used to count the number of times the word “soil” occurs in each document. A distinction was made between “soil” written as a surface area (land use, square meters) and a resource (ecosystem, cubic meters). A further statistical analysis was performed by crossing the results with demographic data and the main characteristics of the documents. Results and discussion The results revealed that soil is a subject which is relatively infrequently addressed in French planning documents. Indeed, its index of occurrence reached 0.06% in comparison to “transport” (0.77%). Moreover, “soil” refers both to a surface area (0.035%) and a resource (0.031%). However, this consideration varies from document to another and depends on the given urban area. Finally, the publication date of the document was correlated with the frequency of the use of the word “soil.” These results suggest that the level of consideration of soil, as a complex ecosystem, is moderate and relies mainly on the people who drafted the document. Conclusions The frequency of the word “soil” is comparable to those of words as “biodiversity” and “air.” Moreover, “soil” is considered as a living resource in the planning documents. It also appears that the services provided by agricultural and forest soils are well known to policy makers and planning operators (e.g., food and non-food biomass provisioning). In contrast, urban soils are predominantly seen as surface areas to be converted or as a potential threat due to their level of contamination or geotechnical properties.